O rzymskich ustawach ograniczających wydatki na organizację uczt (Makrobiusz, "Saturnalia" 3,17) - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper is devoted to the seventeenth chapter of Book Three of Macrobius’ Saturnalia. It features a fragment of a discussion about luxury, which shows how the Roman state tried to limit excessive spending on the organisation of feasts. The paper contains the Latin original with a translation into Polish as well as commentary on e.g. sources used by Macrobius when working on the chapter, and the various leges cibariae meant to curb this form of luxury
Keywords: Makrobiusz. Saturnales; finanse; prawo rzymskie; przyjęcia okolicznościowe